OPTIMALISASI PENGELOLAAN SAMPAH BERBASIS RUMAH TANGGA MENUJU BANTUL BERSIH SAMPAH TAHUN 2025 - suharta, rudy (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
Efforts to improve the effectiveness and efficiency of waste management in Bantul Regency comprehensively in the long term require integrated, integrated and sustainable planning. How is the most effective and can be applied in the community as an effort to manage waste. The purpose of this research is to find out the problems and obstacles as well as the efforts made by the community. The method used in this research is descriptive qualitative research with the scope and object of the community in Murtigading, Sanden, Bantul. Waste management starting from households is very important so that the process of sorting and managing waste is easier and has benefits and has economic value. Strategies and innovations in waste management are carried out through socialization and assistance to the community with non-governmental groups at the hamlet and RT levels to create economic value from waste management. These efforts can further optimize the role of environmental cadres or PKK at the hamlet and RT levels in assisting behavioral awareness at the family level to sort waste. The integrated movement that is integrated in a sustainable manner starting from the segregation of household-scale waste is expected to support the success of the Bantul Bersih Sampah 2025 (Bantul Bersama).